New Public Management to Administrative Effectiveness in Local Administrative Organizations Roi-Et Province - Pipitkun, Kittipong; Kunpalin, Poowanida; Boonmee, Kanokon (Dhammathas Academic Journal, 2019)
This research aims to study: 1) level of new public management affecting the administration of local government organizations in Roi-Et; 2) Analysis of confirmatory factor analysis A New Public Management that affects the effectiveness of local government administration organizations in Roi-Et Province; 3) Create a model of new government management that is effective for the administration of local government organizations in Roi-Et Province. The population used in the research is the administration officials of the local administrative organizations. In Roi-Et Province. Sample group used in research determined from the formula of Taro Yamane, the number of 317 people. The instrument used for data collection is a questionnaire with a confidence value of 0.942. The statistics used in the analysis are frequency, mean, standard deviation, one samples t-test, Pearson’s product moment coefficient of correlation and structural equation analysis. This research aims to study: 1) level of new public management affecting the administration of local government organizations in Roi-Et; 2) Analysis of confirmatory factor analysis A New Public Management that affects the effectiveness of local government administration organizations in Roi-Et Province; 3) Create a model of new government management that is effective for the administration of local government organizations in Roi-Et Province. The population used in the research is the administration officials of the local administrative organizations. In Roi-Et Province. Sample group used in research determined from the formula of Taro Yamane, the number of 317 people. The instrument used for data collection is a questionnaire with a confidence value of 0.942. The statistics used in the analysis are frequency, mean, standard deviation, one samples t-test, Pearson’s product moment coefficient of correlation and structural equation analysis. The research found that: 1. Prepositional factors in each aspect of the assertive element in general. It is high compared to the criteria. Significant at the 0.05 level. 2. Confirmed elements in the following overview. It is important to select factors in the model, equation, structure and criteria. The standard weight of 0.70 and above such as: 2.1) new government management factors include performance appraisal. Participatory management outsourcing organization of learning and use of technology to manage, 2.2) organizational culture: Successful work. Cultivate the values of work Cultivate public mind Introduce new techniques to optimize the use of resources. And the knowledge transfer in the work, 2.3) management competencies include planning. Getting ready for an uncertain situation. ethics of local administrators. The ability of executives to create teams. The ability of executives to provide resources and the vision of local; 2.4) performance management factors, including operational results. Organization development Internal process resources and the ability to create satisfaction. 3. The model of new government management effective to the administration of local administrative organizations in Roi-Et province found that the effectiveness of management was directly influenced by the new government (Direct Path Coefficient = 0.571) and Indirect Path Coefficient = 0.871 and Indirect Path Coefficient = 0.921, respectively.